2014
DOI: 10.1371/journal.pone.0089977
|View full text |Cite
|
Sign up to set email alerts
|

The Role of SGLT1 and GLUT2 in Intestinal Glucose Transport and Sensing

Abstract: Intestinal glucose absorption is mediated by SGLT1 whereas GLUT2 is considered to provide basolateral exit. Recently, it was proposed that GLUT2 can be recruited into the apical membrane after a high luminal glucose bolus allowing bulk absorption of glucose by facilitated diffusion. Moreover, SGLT1 and GLUT2 are suggested to play an important role in intestinal glucose sensing and incretin secretion. In mice that lack either SGLT1 or GLUT2 we re-assessed the role of these transporters in intestinal glucose upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
268
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(286 citation statements)
references
References 37 publications
(78 reference statements)
16
268
1
1
Order By: Relevance
“…Because GLP-1 is a satiety hormone produced in L cells primarily located in more distal sites of the intestine (20)(21)(22), the lower expression of GLUT5 than of SGLT1 at more distal sites would significantly impact the effect of the 2 monosaccharides on GLP-1 release and energy intake. SGLT1 has been found to play a crucial role in glucose-dependent GLP-1 secretion (23,24). The current findings, along with data showing that oral ingestion or intragastric loads of glucose are more effective than fructose in stimulating GLP-1 secretion (4,5), may indicate a greater role of SGLT1 in distal intestinal sites.…”
Section: Discussionsupporting
confidence: 56%
“…Because GLP-1 is a satiety hormone produced in L cells primarily located in more distal sites of the intestine (20)(21)(22), the lower expression of GLUT5 than of SGLT1 at more distal sites would significantly impact the effect of the 2 monosaccharides on GLP-1 release and energy intake. SGLT1 has been found to play a crucial role in glucose-dependent GLP-1 secretion (23,24). The current findings, along with data showing that oral ingestion or intragastric loads of glucose are more effective than fructose in stimulating GLP-1 secretion (4,5), may indicate a greater role of SGLT1 in distal intestinal sites.…”
Section: Discussionsupporting
confidence: 56%
“…It would be of interest to demonstrate expression of SGLT1 and GLUT2 in NT-producing cells by immunohistochemistry. However, SGLT1 has been detected on the luminal process of the GLP-1-producing L cell (6) and in expression analysis of purified murine L cells (23), and, like NT, GLP-1 secretion is sensitive to SGLT1 inhibition (6,17,21,24). By analogy, therefore, we assume that these glucose transporters are also expressed by the NT cells, although a direct investigation of this is warranted.…”
Section: Discussionmentioning
confidence: 98%
“…A few reports have shown that glucose stimulates NT secretion in healthy young humans (18) and from isolated perfused rat small intestine (4), but the underlying mechanisms of secretion are not well understood. Studies of secretion of the gut hormone glucagonlike peptide-1 (GLP-1) have indicated that glucose-stimulated secretion of this hormone involves electrogenic sodium uptake through sodium-glucose transporter 1 (SGLT1) as well as closure of ATP-sensitive potassium (K ATP ) channels (6,17,21,24). Recent findings indicate that some enteroendocrine cells have substantial similarities in respect to expression of glucose transporters and molecular glucose sensors (5, 8).…”
mentioning
confidence: 99%
“…The picture is similar in human neonates with mutations in SGLT1, which causes glucose-galactose malabsorption (Wright et al, 2003). In contrast, GLUT2-null mice, and patients with GLUT2 deficiency, do not exhibit such extensive impairment of glucose absorption (Wright et al, 2003;Roder et al, 2014).…”
Section: Controversy About the Contribution Of Glut2mentioning
confidence: 98%
“…Wright et al (2011) pointed out that phloretin is also a potent non-competitive inhibitor of SGLT1, and so Kellett and Helliwell (2000) underestimated the importance of SGLT1 and thus overestimated the importance of GLUT2. Indeed, subsequent work on both transporters, using wildtype mice and mouse transporter knockouts, indicated that after a high glucose load either some GLUT2 (Gorboulev et al, 2012) or no GLUT2 (Roder et al, 2014) was incorporated into the brush border membrane, but in either case GLUT2 had little or no impact on glucose absorption in comparison to SGLT1. But, as is revealed in the debate related to Naftalin (2014), and even stated in Roder et al (2014), the different findings about the role of GLUT2 in glucose absorption might result from particular diet effects or methods or even species differences, and the controversy may continue.…”
Section: Controversy About the Contribution Of Glut2mentioning
confidence: 99%